Struktura prebiralnih gozdov v raziskovalnem objektu Volčja preža na Goteniški gori - Šubic, Janez (Gozdarski vestnik, 2010)
The Volčja preža research object (a part of the compartment 53) was established in the Forest Management Unit Ravne (Forest Management Region Kočevje) to study structure, regeneration and dynamics of selection-managed Dinaric silver fir-European beech forests. On 45 permanent research plots (each of 500 m2), all trees with dbh ? 10 cm were registered and measured, additionally some tree characteristics were assessed. The regeneration was examined on 180 plots of 1.5 * 1.5 m each. Based on archival data, the dynamics of forest stands were studied in the period 1892-2005. Significant changes of dbh structure and tree species composition were found in the study period. The proportion of silver fir changed noticeably; its proportion had been increasing until 1961 due to harvesting of broadleaves, while after 1961 its proportion was decreasing mainly due to its low vitality and high browsingpressure of large herbivores. The structure of the analyzed forest stands was mainly single-tree, but also group-selection uneven-aged, average growing stock was 420 m3/ha, the proportion of large-diameter trees was high (47 %), the proportion of Norway spruce was significant (14 %). The quality and vitality of all tree species were appropriate and the regeneration was sufficient.
Keywords: gozdovi; prebiralni gozdovi; gozdne ploskve; razvoj gozdov; struktura gozdov